Effects of harvest day after first true leaf emergence of broccoli and radish microgreen yield and quality - Irma Ortiz; Xudong Zhu; Shirin Shakoomahally; Wenyi Wu; Olayanju Kunle-Rabiu; Ellen R. Turner; Tianbao Yang (Technology in Horticulture)
Microgreens are 7−20-d old young vegetables with rich nutrition. In commercial settings, their harvest time varies after first true leaf emerges. To determine the optimal harvest time, the microgreen yield and quality of broccoli (Brassica oleracea var. italica Plenck) and radish (Rhaphanus sativus L.), were analyzed after different harvest times. Under hydroponic culture at 25 °C and 16/8 h photoperiod, the first true leaf of broccoli and radish emerged on day 10 and day 7 respectively. Broccoli harvested at day 13 and radish harvested at day 10, showed significantly highest yield and chlorophyll content compared to that of plants harvested on any other day. The microgreen yield was 20% higher when broccoli and radish were harvested at day 13 and day 10 compared to those harvested on earlier days. The overall visual quality of microgreens stored at 4 °C was evaluated for the extent of decay. There was less visible decay for broccoli harvested at day 13 and radish harvested at day 10. Regarding nutrient quality, there was no significant difference for glucosinolates and total phenolics among different harvested days. However, anthocyanins were decreased significantly for radish harvested at day 11. Overall, the results suggest that the best harvest time for radish and broccoli microgreens is when about 75% true leaves emerge. This research will provide microgreen growers a basis for determining the optimal harvest time of microgreens.